Peran Analisis Laporan Keuangan Dalam Proses Evaluasi Permohonan Kredit: Tinjauan Kasus Di Pt. Bank Rakyat Indonesia (PERSERO) TBK. - Zantomi, Sir; Thahir, Andi; Riswan (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2023)
The most important aspect above when evaluating the performance of a company is its satisfactory financial position. For this reason, companies must manage their financial management carefully and manage it well. Financial ratio analysis is used to analyze financial performance. When analyzing company performance from a financial perspective, ratio analysis is a tool for analyzing financial data contained in financial reports. The analytical method used in this research is a quantitative method which aims to obtain information about various field conditions and interpret them based on interrelated theory and literature. The analytical tools used to analyze customer financial reports include liquidity ratios, solvency ratios and profitability ratios. Based on research results obtained from PT. Bank Rakyat Indonesia (Persero) Tbk., the author concludes that there is a very effective financial report analysis to find out whether banks carry out credit assessments of prospective debtors by using ratio analysis to manage liquidity, profitability and profitability. The financial ratios calculated include the current ratio, quick ratio, debt to equity ratio, debt to equity ratio, profit margin, investment returns and return on equity. Improve and improve the quality of creditor financial report analysis in evaluating credit applications, as a basis for considering and completing further financial ratio analysis.